Pengaruh Senam Diabetes terhadap Kadar Glukosa Darah pada Pasien Diabetes Mellitus di Puskesmas Gunungpati - Vorella Hani Agustin; Virginia Alegra Prameswari; Yosia Putra Pratama; Dwi Yogo Budi Prabowo; Swanny Trikajanti Widyaatmadja; Suksi Riani; Nur Widayatik; Reni Purwandari (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Diabetes mellitus is a chronic metabolic disease characterized by elevated blood glucose levels due to impaired insulin secretion or function. The prevalence of diabetes continues to increase in Indonesia, particularly among adults and the elderly, requiring comprehensive and sustainable management. Diabetes management is not limited to pharmacological therapy but also includes non-pharmacological approaches such as dietary management, physical activity, and health education. One form of physical activity recommended for diabetes sufferers is diabetes exercise. This study aims to determine the effect of diabetes exercise on reducing blood glucose levels in diabetes mellitus patients enrolled in the Chronic Disease Management Program (Prolanis) at the Gunungpati Community Health Center (Puskesmas). The study used a quantitative approach with a one-group pretest-posttest pre-experimental design. A total of 30 respondents were randomly selected from the Prolanis patient population, and blood glucose levels were measured before and after the diabetes exercise intervention. The intervention was carried out routinely and structured over a certain period. The analysis using the Wilcoxon Signed Ranks test showed a statistically significant decrease in blood glucose levels after diabetes exercise, with a p-value of 0.000 (p < 0.05). The average blood glucose level decreased from 260.27 mg/dL to 211.33 mg/dL. This study concluded that diabetes exercise is effective as a non-pharmacological intervention in helping control blood glucose levels. Therefore, routine implementation of diabetes exercise in primary healthcare facilities needs to be promoted as a simple, effective, and affordable promotive and preventive strategy.